The Study of Intelligence Profiles Between Islands: A Preliminary Study Towards Norm Development - Andika Octavianto; Mohammad A. G. Priadi; Magdalena S. Halim; Christiany Suwartono (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
The aim of this study was to compare the intelligence of Indonesians residing in different islands using the Indonesian WAIS-IV (WAIS-IV-ID), which could be further considered in standardized norm development. Statistical analyses using ANOVAs were performed on the 15 subtests, four indices, and the Full-Scale Intelligence Quotient (FSIQ) of the WAIS-IV-ID. This study involved 506 healthy participants, the majority were females, in productive age-groups ranging from 16 to 59 years old, and from middle educational background. Results showed that three indices and 13 subtest scores had significant results and the sample from Java Island had significantly higher scores than the sample from Sumatra, Borneo, and Sulawesi Islands. Based on the conducted analysis, the normative data of the WAIS-IV-ID need to be classified differently between islands or between Java Island and Non-Java Island for more accurate score interpretation. The interpretations and implications of the findings are discussed.